The Implementation of Inspiratory Muscle Training to Enhance Weaning from Mechanical Ventilation: A Systematic Literature Review - Anton Priambodo; Henny Suzanna Mediani; Etika Emaliyawati (The Journal of Palembang Nursing Studies, 2022)
Background: Mechanical ventilation is very important for the world of critical care. However, the use of mechanical ventilation also affected respiratory muscle weakness. Objective: The purpose of this study was to identify the implementation of Inspiratory muscle training for weaning mechanical ventilation in patients with mechanical ventilation in the Intensive Care Unit. Design: A systematic literature review study design was used. Data Sources: The databases used are CINAHL, PubMed, MEDLINE, Sage Journal, and ScienceDirect. Review Methods: Articles published from 2009-2020 with the type of randomized research-controlled trial (RCT) in English. The keywords "Inspiratory Muscle Exercise", "Inspiratory Muscle Training", "weaning", "mechanically ventilated", "critical care", and "intensive care". Results: From four articles analyzed, we found an effect of inspiratory muscle training on ventilator weaning, which was carried out on therapy five times a week, and some were carried out for seven days for two weeks and increased respiratory muscle strength. Conclusion: Inspiratory muscle training in mechanically ventilated patients is a nursing intervention that requires evidence-based preparation of guidelines to provide best practice. The optimalization of inspiratory muscles exercise can help the weaning process and be implemented further.